Pengaruh Self-Esteem terhadap Celebrity Worship pada Penggemar Boygroup Seventeen di Kota Bandung - Anggita Shafa Audria; Yanuvianti, Milda (UNISBA Press, 2024)
Abstract. The phenomenon of celebirty worship of Korean idols has become an important part of today's popular culture, especially in adolescence and emerging adulthood. One of the South Korean boy groups that is currently popular and much loved is SEVENTEEN. Every fan has varying levels of engagement with their idols, ranging from admiration to obsession that can affect daily life. One factor that is thought to have a significant role in the onset of celebrity worship is self-esteem. This study aims to determine the effect of self-esteem on celebrity worship in Seventeen boy group fans in Bandung City. This research is a quantitative research with causality method. The measuring instruments used are the Celebrity Attitude Scale (CAS) which has been adapted by Efathania & Aisyah (2019) and the Rosenberg Self-esteem Scale (RSE) adapted by Nelan Maroqi (2018). The subjects of this study were Seventeen boy group fans aged 18-29 years and domiciled in Bandung City with the number of respondents obtained as many as 311. This research hypothesis test uses simple linear regression analysis and the results obtained show that there is a negative effect of self-esteem on celebrity worship with a significance value of 0.002 <0.05, which means that low self-esteem will result in high celebrity worship, and vice versa. The magnitude of the influence of self-esteem on celebrity worship is 2.9%. This finding indicates that self-esteem can influence celebrity worship but the contribution is relatively small. Abstrak. Fenomena celebirty worship pada idol korea telah menjadi bagian penting dari budaya populer masa kini, terutama pada usia remaja dan emerging adulthood. Salah satu boygroup korea selatan yang tengah populer dan banyak digemari saat ini adalah SEVENTEEN. Setiap penggemar memiliki tingkat keterlibatan dengan idola mereka yang bervariasi, mulai dari kagum hingga obsesi yang dapat mempengaruhi kehidupan sehari-hari. Salah satu faktor yang diduga memiliki peran signifikan dalam timbulnya celebrity worship adalah self-esteem. Penelitian ini bertujuan untuk mengetahui pengaruh self-esteem terhadap celebrity worship pada penggemar boygroup Seventeen Di Kota Bandung. Penelitian ini merupakan penelitian kuantitatif kausalitas. Alat ukur yang digunakan adalah Celebrity Attitude Scale (CAS) yang diadaptasi oleh Efathania & Aisyah (2019) serta Rosenberg Self-esteem Scale (RSE) yang diadaptasi oleh Nelan Maroqi (2018). Subjek penelitian ini adalah penggemar boygroup Seventeen berusia 18 – 29 di Kota Bandung dengan jumlah responden yang diperoleh sebanyak 311. Uji hipotesis penelitian menggunakan analisis regresi linear sederhana dan hasil yang didapat menunjukkan bahwa terdapat pengaruh negatif self-esteem terhadap celebrity worship dengan nilai signifikansi 0.002 < 0.05, yang berarti self-esteem rendah akan menghasilkan celebrity worship yang tinggi, begitupula sebaliknya. Adapun besaran pengaruh self-esteem terhadap celebrity worship adalah sebesar 2.9%. Temuan ini mengindikasikan bahwa self-esteem dapat berpengaruh terhadap celebrity worship namun konrtibusi nya relatif kecil.